Птицы лесных насаждений центральных районов Кубы - Сантос, Антонио Хосе; Таращук, В.И. (Вестник зоологии, 1981)
Nowadays comparatively low-productive forests in the central regions of Cuba number about 40 species of woody and shrubby birds. About a hall of them is insectivours and partially insectivorous birds, the rest - are mainly phytophagous. The species diversity and population density are higher in the remained areas of the natural forest and shrubby thickets in Daces of old glades. To preserve and increase the amount of useful birds it is necessary to create forbidden zones.